IMPLEMENTASI TANGGUNG JAWAB SOSIAL PERUSAHAAN PT. TIRTA INVESTAMA DANONE AQUA DALAM PEMBERDAYAAN MASYARAKAT DI KANAGARIAN BATANG BARUS KAYU ARO KABUPATEN SOLOK - Yulia Risa; Elwidarifa Marwenny (STIH Putri Maharaja, 2018)
By paying attention to CSR, the company is not only oriented to the finance of the corporate (single bottom line), but also focuses on the balance between financial aspects, social aspects and environmental aspects (triple bottom line). The synergy of these three keys is the concept of sustainable development and community empowerment . This study has three aims. First, to describe and analyzed the regulation of CSR in companies engaged in natural resources. Second, to describe and analyzed the innovation of CSR strategies used by PT. Tirta Investama Danone Aqua in Empowering the communities in Kanagarian Batang Barus Kayu Aro. Third, to describe and analyzed the factors that hamper the development of CSR strategy by PT. Tirta Investama danone Aqua. This study uses an empirical juridical research method to see how the company engaged in natural resources apply the strategies and principles of Corporate Social Responsibility in realizing the community empowerment around the company. The final result that will be achieved is the CSR program by PT. Tirta Investama Kayu Aro will have a better focus on the community development and suistanable environmental development. The implementation of CSR strategic are taken by PT. Tirta Investama Danone Aqua Plan Solok. The implementer of the program entrusted to The Indonesian Family Planning Association (PKBI) in West Sumatra Province. This institution shall be responsible in conducting the CSR strategies in the society and community located around the company location.